Democracy in Cage: Towards a Framework for a State Restructuring in Nepal - Pandey, Tulsi Ram (Occasional Papers in Sociology and Anthropology, 2010)
"State Restructuring" has appeared as one of the important issues currently in vogue in public debates of Nepal. The "People's War" waged by Maoist political organization against existing system of governance has been the most important contributory factor to initiate this type of debate. The failure of existing state organization to settle the issues raised by people by way of this rebellion is also equally responsible for further stimulating this debate. However, a chain of political events happened in the country in a series of sequences during the period covered by this rebellion. Consequently, there has been a progressive growth in the number of participants involved in this debate and the type of demand posed by them towards restructuring the state. DOI: 10.3126/opsa.v11i0.3035 Occasional Papers in Sociology and Anthropology Vol.11 2009 148-177